Personality, affect, and behavior in groups revisited: Comment on aggregation, levels of analysis, and a recent application of within and between analysis. - George, Jennifer M.; James, Lawrence R. (Journal of Applied Psychology, 1993)
Recently, F. J. Yammarino and S. E. Markham (1992) summarized the basic within and between analysis (WABA) approach, applied it to data previously collected and reported on by J. M. George (1990), and used this application to critique George's findings. After briefly reviewing the theoretical underpinnings of George, the authors discuss several points of confusion in Yammarino and Markham's article in regard to the determination of the appropriateness of aggregation and the existence of relations between variables at the group level of analysis. The authors then discuss several short-comings in Yammarino and Markham's description of WABA, including the failure to consider Person × Situation interactions in the basic WABA equation and misinterpretations of comparisons of the within component to the between component in WABA